2017
DOI: 10.1080/1828051x.2017.1393320
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the dry and the rainy season on endocrine and physiologic profiles of goats in the Brazilian semi-arid region

Abstract: This study investigated the effect of season on the endocrine and adaptive profiles of a Brazilian Creole goat population in a semi-arid region of Brazil during the dry and the rainy season. We considered physiological, morphological, biochemical, haematological, hormonal and anatomical profiles. The experiment used 80 adult goats (2-to 5-year-old) and lactating (160 ± 14 days of lactation length) goats, with an average daily milk yield of 500.9 ± 13 g. Physiological parameters (rectal temperature, RT; respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
24
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 30 publications
10
24
0
3
Order By: Relevance
“…Al-Eissa et al (2012) observed higher Glb concentration in Nubian goats under cold climatic conditions that led to decreased Alb: Glb ratio. In this line, Ribeiro et al (2018) reported that differences in globulin values are related to physiological and genetic factors of animal adaptation.…”
Section: Blood Biochemical Parametersmentioning
confidence: 99%
“…Al-Eissa et al (2012) observed higher Glb concentration in Nubian goats under cold climatic conditions that led to decreased Alb: Glb ratio. In this line, Ribeiro et al (2018) reported that differences in globulin values are related to physiological and genetic factors of animal adaptation.…”
Section: Blood Biochemical Parametersmentioning
confidence: 99%
“…It is a more specific indicator of PLT activation since it is not elevated during single PLT distention caused by PLT swelling (Vagdatli et al 2010 However, in this study, hematological parameters seem to be most damaged in black coat color goats. According to Ribeiro et al (2018), animals alter hematological parameters to maintain a stable body temperature, i.e., to maintain RT and PR within the limits recommended for this species and they adjust these parameters to survive both food and water shortages as well as high temperatures. This seem to be normal as the black coat color goats were most affected with physiological parameters as well as food and water consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of haematological indices can be an important tool of checking on animal welfare, since blood is an important response indicator to climatic changes (Okourwa 2015). Ribeiro et al (2018) noted that thermal conditions, especially those associated with seasonal periodicity, may directly affect the changes in blood indices. Significant differences between the WBC, NEU, RBC, MCV, MCH, and PLT values between the THI groups were determined.…”
Section: Discussionmentioning
confidence: 99%
“…Climatic variations directly affect the animals, changing their physiology (Ribeiro et al 2018). The impact of climatic changes has caused much loss in livestock production (Salama et al 2014) -a fact that generates the need for detailed studies to better understand the mechanisms of animal adaptation to a changing climate.…”
mentioning
confidence: 99%
See 1 more Smart Citation